TREN PENELITIAN DALAM PEMBANGUNAN BERKELANJUTAN Perkembangan Mobilitas Cerdas Dan Transportasi Cerdas: - , Devi Naily Fadlilah; Achmad Nurmandi; Helen Dian Fridayani (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2024)
This research is motivated by the development of the Smart City concept as a sustainable development step in Indonesia. One of the projects of the Smart City concept is Smart Mobility. Smart Mobility in urban transportation is the concept of utilizing technology to improve the effectiveness, efficiency and sustainability of transportation by considering various impacts on the environment. The purpose of this study is to determine the development of smart mobility-based transportation. The method used in this research is a bibliometric analysis that will examine publication trends related to urban transportation. The results of this study show that the concept of smart mobility has the potential to improve sustainable development in Indonesia, especially in terms of transportation efficiency, effectiveness, and sustainability. However, in its implementation, urban transportation with the concept of smart mobility still has gaps, namely for conventional transportation service providers in the existence of conventional ojek performance in the midst of digital-based transportation business competition. In conclusion, this research analyzes the development of smart mobility and provides several solutions for conventional transportation service owners. So that this research can be a reference for the authorities to make some efforts in maximizing the concept of smart mobility.